PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, OPINI AUDITOR , DAN UKURAN KANTOR AKUNTAN PUBLIK TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI BEI TAHUN 2012-2014 - Ratry Martharima Wulandari; Azwir Nasir; Susilatri Susilatri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to attest empirically the effect of profitability, leverage, company size, audit opinion and the size of the accounting firm on the audit report lag in consumer goods companies listed in Indonesia Stock Exchange in 2012-2014. Samples were taken by using purposive sampling. From all the consumer goods company listed in Indonesia Stock Exchange, acquired 24 companies that meet criteria for sampling with a period of three years, so the total sample ini this research was 72. The data analysis method used in this research is multiple regression analysis were processed using SPSS 21 . The results of hypothesis testing found that, size of the public accounting firm negatively affect audit report lag with a significant value of 0.014. While profitability, leverage, firm size and audit opinion has no effect on audit report lag. Coefficient determination test results in this study showed R2 value of 0.155. It shows that the contribution of the influence of the independent variable on the dependent variable is 15.5%. While the remaining 84.5% is influenced by other variables not included in the regression model.keywords: audit report lag,profitability,leverage, company size, auditor opinion, size of the accounting firm